Periprocedural imaging compared to endometrial biopsy: is biopsy required prior to uterine artery embolisation?. Issue 9 (September 2022) - Currie, B.M.; McLaughlin, S.W.; Jones, L.; Neff, P.; Shlansky-Goldberg, R.D.
Abstract : Aim: To compare the detection rate of magnetic resonance imaging (MRI) and ultrasound relative to endometrial biopsy for endometrial abnormalities in both pre- and post-menopausal women. Materials and methods: The present study was an institutional review board-approved, single-institution retrospective analysis of patients who underwent pelvic MRI within 1 year of diagnostic-quality biopsies from 2008–2018 (n=668). There were 303 patients who received uterine artery embolisation (UAE) and 478 patients who received pelvic ultrasound within the study period. Medical records were evaluated for radiological–histopathological correlation, demographics, laboratory studies, and clinical follow-up. Results: In this cohort of 668 patients, there were 37 biopsies positive for malignancy; women with malignancy were older (58 versus 47 years, p < 0.0001) and more likely to be post-menopausal (66% versus 12%, p<0.0001). There were 303 patients who underwent UAE and underwent a diagnostic-quality endometrial biopsy during the pre-procedural evaluation, none of whom were post-menopausal and had a mean age of 45 years. In women with abnormal uterine bleeding (AUB) or post-menopausal bleeding (PMB), the sensitivity of MRI for detecting endometrial cancer was 96.2%, with a negative predictive value (NPV) of 99.8%, compared to 68% and 97% for ultrasound, respectively. The receiver operating characteristic (ROC) curve of pre-biopsy MRI in identifying pre-malignant and malignant endometrial pathology demonstrated an AUC of 0.8920 (p<0.0001). Conclusion: In women with AUB or PMB, MRI has a 99.8% NPV in ruling out endometrial cancer. Further consideration should be made towards optimising pre-procedural evaluation for UAE. Highlights: MRI is highly accurate in detecting endometrial pathology compared to biopsy. Pelvic MRI can identify important extra-endometrial pathology. Low prevalence of endometrial cancer in patients referred for UAE. Preprocedural evaluation for UAE may be further refined to optimize patient care.